Dorr tanks at Dow Chemical Company plant - Dow Chemical Company (1952)
General view of the Dorr sewage treatment tanks at the Dow Chemical Company plant located in Freeport, Texas.
Keywords: Sewage; Industries; Dow Chemical Company; Sewage disposal plants